2022
DOI: 10.1021/acsomega.2c02190
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Surfactant Stripping Crude Oil and Spontaneous Imbibition Mechanism of Surfactants in a Tight Reservoir

Abstract: Surfactants play a vital role in the working fluid during the exploitation of tight reservoirs. The main goal is to clarify the mechanism of surfactant production enhancement in the reservoir. In this paper, starting from the interface properties and emulsifying properties of surfactants, the factors affecting the stripping of crude oil by different surfactants were described in detail. Meanwhile, the imbibition experiments of cores were used to clarify the two spontaneous imbibition mechanisms of the surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The demulsification of crude oil emulsion was performed by negative ions. 29 While the role of positive ions was to deform the water droplets, thereby promoting the destruction of the emulsion. Low-valent metal salt ions react with alkyl carboxylate in crude oil to generate metal soaps, which promotes the deformation of water droplets.…”
Section: Resultsmentioning
confidence: 99%
“…The demulsification of crude oil emulsion was performed by negative ions. 29 While the role of positive ions was to deform the water droplets, thereby promoting the destruction of the emulsion. Low-valent metal salt ions react with alkyl carboxylate in crude oil to generate metal soaps, which promotes the deformation of water droplets.…”
Section: Resultsmentioning
confidence: 99%
“…[4,5] A significant fraction of the remaining oil within the rock pores is microscopically trapped due to capillary barriers induced by the complex structure inside the pores of rocks. [6][7][8] By reducing the interfacial tension (IFT) between the displacing fluid and oil, the surfactant can facilitate mobilization of the oils trapped in the rock pores. [9][10][11] In addition, surfactants are capable of changing the wetting state of the rock surface from oil-wet toward a neutral-or water-wetting state so that attached oils on the rock surfaces can be released and moved toward the production well.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 The imbibition action of the microemulsion can force the oil into the tight matrix. 19 According to Sharma and Sheng et al, 20 , 21 the imbibition of a low permeability core in surfactant solution (IFT is around 1 mN/m) is a reverse flow process by CT scanning (oil flows out of the pores), implying that capillary force dominates the process. Tagavifar et al 22 used numerical simulation to reveal surfactant adsorption kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous decline of the conventional reserves, exploration of the tight and low permeability reservoirs has become a trend. , Hydraulic fracturing stimulation has emerged as a critical method for extracting these types of hydrocarbon resources. , The purpose of hydraulic fracturing is to increase the fluid seepage area and convert radial flow into linear flow in order to reduce seepage resistance. The surfactant is also widely utilized in oil production of low-permeability reservoirs as a low-cost working fluid that can reduce oil–water interfacial tension, change wettability, and increase oil–water emulsification. Several studies indicate that fracturing fluid imbibition on the reservoir fracture surface is one of the core processes of enhanced oil recovery (EOR). Through the visualization model experiment, some researchers have shown that when the interfacial tension is reduced to ultralow, the surfactant and oil generate microemulsions during the displacement process. , The imbibition action of the microemulsion can force the oil into the tight matrix . According to Sharma and Sheng et al, , the imbibition of a low permeability core in surfactant solution (IFT is around 1 mN/m) is a reverse flow process by CT scanning (oil flows out of the pores), implying that capillary force dominates the process.…”
Section: Introductionmentioning
confidence: 99%